2022
DOI: 10.3389/fonc.2022.934928
|View full text |Cite
|
Sign up to set email alerts
|

A novel m7G-related lncRNA risk model for predicting prognosis and evaluating the tumor immune microenvironment in colon carcinoma

Abstract: N7-Methylguanosine (m7G) modifications are a common type of posttranscriptional RNA modifications. Its function in the tumor microenvironment (TME) has garnered widespread focus in the past few years. Long non-coding RNAs (lncRNAs) played an essential part in tumor development and are closely associated with the tumor immune microenvironment. In this study, we employed a comprehensive bioinformatics approach to develop an m7G-associated lncRNA prognostic model based on the colon adenocarcinoma (COAD) database … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Recently, the role of lncRNA in m 7 G and their relationship to cancer were gradually clear. For example, some researchers have identified that the m 7 G-related lncRNA risk model can be an efficient prognostic tool and anti-tumor immunotherapy target for multiple cancer types, including colon carcinoma, 34 Lung Adenocarcinoma 35 and cutaneous melanoma. 36 In our study, the m 7 G-related lncRNAs risk model was constructed using three prognostic lncRNAs by bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of lncRNA in m 7 G and their relationship to cancer were gradually clear. For example, some researchers have identified that the m 7 G-related lncRNA risk model can be an efficient prognostic tool and anti-tumor immunotherapy target for multiple cancer types, including colon carcinoma, 34 Lung Adenocarcinoma 35 and cutaneous melanoma. 36 In our study, the m 7 G-related lncRNAs risk model was constructed using three prognostic lncRNAs by bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Age, lactate dehydrogenase (LDH) level, cell-of-origin, extranodal sites, and Eastern Cooperative Oncology Group performance status were correlated clinicopathological variables used in nomogram construction. Sheng Yang et al [ 83 ] identified eight N7-methylguanosine-related lncRNAs (consisting of ELFN1-AS1) and established a risk signature derived from TCGA and validated it in GEO (GSE17536 dataset) database patients with colon cancer. Based on the risk score and cluster analysis, patients were divided into three groups, of which group 1 had the worst prognosis.…”
Section: Elfn1-as1 Clinical Implicationmentioning
confidence: 99%
“…Yang et al developed eight risk models of m7G-related lncRNAs (ELFN1-AS1, PCAT6, etc.) to predict colon cancer prognosis and assess the tumour immune microenvironment [25].…”
Section: Drug Sensitivity Analysis Of Risk Modelmentioning
confidence: 99%